Pengaruh Pemberian Teknik Relaksasi Nafas Dalam Terhadap Penurunan Nyeri pada Pasien Post OP Fraktur Femur - Wiwi Kustio Priliana; Ni Ketut Kardiyudiani (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2014)
Background: The addition of roads and the use of motor vehicles cause disproportionate number of victims of traffic accidents increased, but the increase in the highest number occurs more frequently in developing countries. The high number of accidents causing higher fracture rates, and one of the conditions most frequently occurring fracture is a fracture of the femur, which belongs to a group of three large cases of fracture caused by a traffic accident and had to undergo surgery with consequent effects obtained pain after surgery. Objective: To investigate the effect of deep breathing relaxation techniques to decrease pain levels in patients with postoperative femoral fracture Methods: The experimental approach to sampling and design purpusif pairod t-test and independent t-test to determine the effect of deep breathing on pain in patients with postoperative femoral fracture.Results: The mean is given before and after a deep breath and do not give a breather in the treatment group compared with the control group showed that the results of the treatment group decreased by 2.8 points, 95% CI = - (3:55 to 2:04) t = -7.6 p = 0:00. This means that there is a significant difference in the mean difference in pain reduction between the groups were given a deep breath than those not given a deep breath. Conclusion: After doing research on getting the results that deep breathing relaxation techniques can reduce postoperative pain in patients with fractures of the femur.